Faecal microbiota transplantation for Clostridium difficile‐associated diarrhoea: a systematic review of randomised controlled trials. Issue 4 (14th August 2017) - Moayyedi, Paul; Yuan, Yuhong; Baharith, Harith; Ford, Alexander C
Abstract: Objectives: Faecal microbiota transplantation (FMT) has emerged as a useful approach for treating Clostridium difficile ‐associated diarrhoea (CDAD). Randomised controlled trials (RCTs) have recently evaluated its effectiveness, but systematic reviews have focused on evidence from case series. We therefore conducted a systematic review and meta‐analysis of RCTs evaluating the effectiveness of FMT for treating CDAD. Study design: We included RCTs that primarily recruited adults with CDAD and compared the effectiveness of FMT with that of placebo, antibiotic therapy, or autologous stool transplantation, or compared different preparations or modes of delivery of FMT. Dichotomous symptom data were pooled to calculate a relative risk (RR) of CDAD persisting after therapy, and the number needed to treat (NNT). Data sources: MEDLINE, EMBASE, and the Cochrane Controlled Trials Register and Database of Systematic Reviews were searched to 6 February 2017. Data synthesis: We identified ten RCTs that evaluated the treatment of a total of 657 patients with CDAD. Five RCTs compared FMT with placebo (including autologous FMT) or vancomycin treatment (total of 284 patients); FMT was statistically significantly more effective (RR, 0.41; 95% CI, 0.22–0.74; NNT, 3; 95% CI, 2–7). Heterogeneity across studies was significant ( I 2 = 61%); this heterogeneity was attributable to the mode of delivery of FMT, and to the therapy being more successful in European than in North American trials. The other five RCTs evaluated different approaches to FMT therapy. Frozen FMT preparations were as efficacious as fresh material in one RCT, but the numbers of patients in the remaining RCTs were too small to allow definitive conclusions. Conclusions: Moderate quality evidence from RCT trials indicates that FMT is more effective in patients with CDAD than vancomycin or placebo. Further investigations are needed to determine the best route of administration and FMT preparation.